Pembelajaran Seni Budaya (Pianika) Menggunakan Media Audio Visual di Kelas VIII-2 SMPN 7 Binjai Provinsi Sumatera Utara - Guido Efran Simanjuntak; Harisnal Hadi (FBS Universitas Negeri Padang, 2022)
The purpose of this study is to describe the implementation of Pianika practice learning using audiovisual media in class VIII-2 at SMPN 7 Binjai. Type of qualitative research with descriptive methods. Research instruments are researchers themselves and are assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out utilizing library studies, observations, interviews, and documentation. The steps of analyzing data are identifying data, classifying data, and inferring data. The results showed that the implementation of Pianika learning using audiovisuals in class VIII-2 went very well, although the Pianika learning process using audiovisuals face-to-face was attended by 50% of students in class VIII-2. It is stated very well because the results of learning to play Pianika in class VIII-2 exceed the KKM value of 72. With a 100% percentage of grades students get a score above KKM or the lowest score of 75 with a percentage of 80% grades that get a score above 75 in class VIII-2 junior high school N 7 Binjai.